Dynamics of Development of Cultural Processes - Ikrom Bobokulovich Mirzayev (Scientific Trends, 2025)
The article scientifically analyzes the historical formation of cultural processes, their inextricable connection with socio-economic, political and spiritual factors, and the dynamics of development in the modern era. The stages of cultural development, their variability and impact on the life of society are highlighted.
Keywords: Culture, cultural process, dynamic development, social progress, values, globalization.